1997
DOI: 10.1073/pnas.94.17.9434
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyfullerenes as neuroprotective agents

Abstract: Biochemistry. In the article ''Identification by mass spectrometry of the phosphorylated residue responsible for activation of the catalytic domain of myosin I heavy chain kinase, a member of the PAK͞STE20 family'' by Joanna Szczepanowska, Xiaolong Zhang, Christopher J. Herring, Jun Qin, Edward D. Korn, and Hanna Brzeska, which appeared in number 16, August 5, 1997, of Proc. Natl. Acad. Sci. USA (94,(8503)(8504)(8505)(8506)(8507)(8508), the authors wish to note that in Fig. 3, the ions of m͞z 1345.3 and 1247.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
455
4
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 715 publications
(471 citation statements)
references
References 39 publications
(40 reference statements)
10
455
4
2
Order By: Relevance
“…tection by C 3 fullerene against excitotoxic, apoptotic, and metabolic insult was observed in cortical cell cultures (97,98). A C 3 fullerene, given orally at 10 mg=kg=day, starting at 12 months of age until death reportedly extended both the life span and cognition of mice; the authors also reported the mitochondrial localization of C 3 and its ability to cross the blood-brain barrier (256,137).…”
mentioning
confidence: 88%
“…tection by C 3 fullerene against excitotoxic, apoptotic, and metabolic insult was observed in cortical cell cultures (97,98). A C 3 fullerene, given orally at 10 mg=kg=day, starting at 12 months of age until death reportedly extended both the life span and cognition of mice; the authors also reported the mitochondrial localization of C 3 and its ability to cross the blood-brain barrier (256,137).…”
mentioning
confidence: 88%
“…Water-soluble fullerene derivatives have shown promise as drug carriers to bypass the brain and ocular barriers (Calvo et al, 1996;Da Ros and Prato, 1999;Dugan et al, 1997). They have also exhibited antitumor and antiviral activity, including inhibition of HIV protease (Bogdanovic et al, 2004;Friedman et al, 1993;Nakamura and Isobe, 2003;Schinazi et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…We used three different free radicals scavengers to assess the role of ROS in cisplatin-induced apoptosis. C 60 (D3) is an effective scavenger of hydroxyl and superoxide radicals (Dugan et al, 1997;Hsu et al, 1998), MnTBAP is a superoxide dismutase mimic, and N-acetylcysteine (NAC) detoxifies free radicals to prevent DNA damage (Malins et al, 2002). C 60 (D3) effectively suppressed apoptosis induced by g-irradiation and cisplatin (Figure 7b).…”
Section: Ros Are Required For Cisplatin-induced Apoptosismentioning
confidence: 99%
“…FITCconjugated anti-Fas antibody, human Fas-Fc, His-tagged FasL, and anti-His antibody were purchased from R&D (Minneapolis, MN, USA). The regioisomer with D3 symmetry of water-soluble carboxylic acid C 60 derivatives (carboxylfullerenes) was synthesized as previously described (Dugan et al, 1997). Dichlorodihydrofluorescein diacetate (DCFCA) and dihydroethidium (DHE) were obtained from Molecular Probes (Eugene, OR, USA).…”
Section: Reagentsmentioning
confidence: 99%